Acinic Cell Carcinoma-Papillary Cystic Variant with numerous psammoma body: A Case Report - Daniyah Saleh, MD, Doaa Al ghamdi*, MD (Innovative Journal of Medical and Health Sciences, 2019)
Acinic cell carcinoma (ACC) is a rare, low-grade malignant salivary gland neoplasm. Parotid gland is the most common location reaching up to 90% of cases. Papillary cystic variant (PCV) is a much more seldom subtype of ACC. Proper diagnosis of ACC-PCV is only made on histopathology examination. The presence of psammoma body in salivary gland lesions is infrequent finding that may be confused with other benign or malignant lesions. The present case describes ACC-PCV in a 31-year-old Saudi male patient referred to King Abdulaziz University Hospital as post superficial parotidectomy which the patient underwent 3 months ago. This case emphasizes the importance of distinguishing between neoplastic and non-neoplastic lesions with numerous psammoma bodies. Key words: papillary cystic acinic cell carcinoma–psammoma body–histopathology– parotid gland.